Artificial Intelligence in Aviation Vocational Training: Mapping Legal Frameworks and Institutional Readiness in Indonesia - Adhitya Octavianie; Ahmad Rossydi; Muh. Agung Raharjo; Nining Idyaningsih; Sukarman Sukarman (International Journal of Artificial Intelligence Research, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in higher and vocational education, yet its rapid adoption often outpaces existing legal and institutional frameworks. This study investigates how Indonesia’s regulatory landscape supports the integration of AI in teaching and learning at Politeknik Penerbangan Makassar (Poltekbang Makassar), and identifies the legal, ethical, and governance challenges shaping responsible innovation. Employing a qualitative descriptive approach, the research combines document analysis of key national policies (such as the National Education System Law 2003, Presidential Regulation No. 95/2018, and the National AI Strategy 2020–2045) with semi-structured interviews involving five lecturers and two academic policymakers. Data were analyzed thematically. The results reveal that while Indonesia’s legal foundations implicitly support AI adoption through broader digital transformation policies, significant regulatory gaps persist, particularly concerning algorithmic transparency, accountability, and data privacy. Institutional policies at Poltekbang Makassar demonstrate readiness for technological innovation but lack comprehensive AI governance mechanisms. The study proposes a multi-level regulatory model encompassing national policy formulation, sectoral alignment within vocational standards, and internal institutional governance frameworks to ensure accountability, fairness, and compliance. These findings contribute to the development of an Institutional AI Governance Framework based on principles of accountability, transparency, and compliance with the Personal Data Protection Law, offering a practical roadmap for policymakers and educational leaders in Indonesia’s vocational sector.Keywords: Artificial Intelligence (AI), AI Governance, Vocational Education, Poltekbang Makassar, Algorithmic Accountability